2019
DOI: 10.1021/acs.joc.9b00988
|View full text |Cite
|
Sign up to set email alerts
|

Gold-Catalyzed Hydroamination of Propargylic Alcohols: Controlling Divergent Catalytic Reaction Pathways To Access 1,3-Amino Alcohols, 3-Hydroxyketones, or 3-Aminoketones

Abstract: A versatile approach to the valorization of propargylic alcohols is reported, enabling controlled access to three different products from the same starting materials. Firstly, a general method for the hydroamination of propargylic alcohols with anilines is described using gold catalysis to give 3-hydroxyimines with complete regioselectivity. These 3-hydroxyimines can be reduced to give 1,3-aminoalcohols with high syn selectivity. Alternatively, by using a catalytic quantity of aniline, 3-hydroxyketones can be … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 121 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…The selectivity issue regarding this reaction is also much more intricate than in the case of alkyne hydration and hydroalkoxylation. First of all, the reaction regioselectivity follows the general trends already outlined for the previous reactions: thus, reaction with terminal alkynes generally exhibits Markovnikov selectivity, whereas lower selectivity is observed with unsymmetrically substituted internal alkynes, unless substituents are present on the alkyne substrate which strongly differ for their stereoelectronic properties or which possess functional groups that direct the nucleophilic attack preferentially toward one of the carbon atoms [76][77][78]. Another important selectivity issue arises when nucleophiles with stoichiometry RNH 2 or RR'NH are employed (Scheme 12), since only the former generates the corresponding imine, whereas the product of the latter is the corresponding enamine.…”
Section: Hydroaminationmentioning
confidence: 62%
See 2 more Smart Citations
“…The selectivity issue regarding this reaction is also much more intricate than in the case of alkyne hydration and hydroalkoxylation. First of all, the reaction regioselectivity follows the general trends already outlined for the previous reactions: thus, reaction with terminal alkynes generally exhibits Markovnikov selectivity, whereas lower selectivity is observed with unsymmetrically substituted internal alkynes, unless substituents are present on the alkyne substrate which strongly differ for their stereoelectronic properties or which possess functional groups that direct the nucleophilic attack preferentially toward one of the carbon atoms [76][77][78]. Another important selectivity issue arises when nucleophiles with stoichiometry RNH 2 or RR'NH are employed (Scheme 12), since only the former generates the corresponding imine, whereas the product of the latter is the corresponding enamine.…”
Section: Hydroaminationmentioning
confidence: 62%
“…These obviously different products have their own chemical behavior and can also evolve differently under reaction conditions. For example, imines are prone to hydrolysis and in the presence of traces of water provide the corresponding ketone; this reaction sequence can be conceived as a strategy to develop an amine-assisted hydration of alkynes [78]. Furthermore, it has been demonstrated that in the presence of excess alkyne the hydroamination product can undergo further reactions such as multiple hydroamination (with the enamine as HNu) [79], or, in the case of terminal alkynes, cycloaddition reactions (Scheme 14) [80].…”
Section: Hydroaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…To synthesize various γ-hydroxy ketones 41 in the presence of efficient gold catalysts, Sheppard proposed adding 0.2 equiv of 3-trifluoromethylaniline 40 to the reaction medium to avoid the Meyer–Schuster rearrangement (Scheme ).…”
Section: Hydration Of (Homo)propargylic Derivativesmentioning
confidence: 99%
“…Laserna et al 147 developed gold-catalyzed reactions of hydroxy-alkynes with anilines to efficiently prepare a series of β-aminoketones 123 (Scheme 42). The mechanism of the reactions, in this case, is related to the efficiency of the catalyst to enable the Meyer–Schuster rearrangement 148 of the propargylic alcohols in the first step, and then the conjugated addition of the primary amine to the generated enones.…”
Section: Synthetic Approachesmentioning
confidence: 99%